2008
DOI: 10.2478/s11756-008-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability within isolates of Colletotrichum lindemuthianum belonging to race 65 from the state of Minas Gerais, Brazil

Abstract: Colletotrichum lindemuthianum, the causal agent of anthracnose in the common bean (Phaseolus vulgaris), presents a wide genetic and pathogenic variability that gives rise to complications in the development of resistant bean cultivars. The aim of this study was to identify the variability within race 65 of C. lindemuthianum, the race most commonly encountered in Brazil, through randomly amplified polymorphic DNA (RAPD) and anastomosis analyses. Thirteen isolates of race 65, collected in different years and fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Incompatibility could be a mechanism of self-defense (Glass et al, 2000). The large number of anastomosis groups was in agreement with the results obtained by RodriguezGuerra et al (2003) and Ishikawa et al (2008), who showed variability for the isolates of C. lindemuthianum studied and a great variation in the number of anastomosis groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Incompatibility could be a mechanism of self-defense (Glass et al, 2000). The large number of anastomosis groups was in agreement with the results obtained by RodriguezGuerra et al (2003) and Ishikawa et al (2008), who showed variability for the isolates of C. lindemuthianum studied and a great variation in the number of anastomosis groups.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have been done for the common bean fungus Colletotrichum lindemuthianum, from which several anastomosis groups have been identified in natural populations (Rodríguez-Guerra et al, 2003;Ishikawa et al, 2008). According to the authors, the occurrence of anastomosis could be an important mechanism that can lead to the formation of different lineages of C. lindemuthianum.…”
Section: Angular Leaf Spot Of Common Bean (Phaseolus Vulgaris L) Is mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Ishikawa, Souza, and Davide (2008) worked with 13 isolates of race 65 from the State of Minas Gerais from different regions and years and used RAPD analysis to identify 11 groups with the phylogenetic tree, which demonstrates the presence of variability within race 65. Santos, Antunes, Rey, and Rosseto (2008) reported pathogenic variability within isolates of race 65, 73 and 81, and two isolates of the same race were inoculated into 37 cultivars used in this study.…”
Section: Similarity and Dissimilarity Measuresmentioning
confidence: 99%
“…The most economically viable and effective strategy for disease control is by using bean cultivars resistant to fungi (Ishikawa et al, 2008). However, this kind of management is difficult to implement due to the high pathogenic variability of C. lindemuthianum (Ishikawa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%